2019
DOI: 10.3390/mi10070438
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Woven Triboelectric Nanogenerator Utilizing Electrospun PVDF Nanofibers for Mechanical Energy Harvesting

Abstract: Several wearable devices have already been commercialized and are likely to open up a new life pattern for consumers. However, the limited energy capacity and lifetime have made batteries the bottleneck in wearable technology. Thus, there have been growing efforts in the area of self-powered wearables that harvest ambient mechanical energy directly from surroundings. Herein, we demonstrate a woven triboelectric nanogenerator (WTENG) utilizing electrospun Polyvinylidene fluoride (PVDF) nanofibers and commercial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 38 publications
0
52
0
Order By: Relevance
“…When the difference between two materials is bigger, the corresponding charge transfer amount is larger, and the output of the prepared TENG is higher. The triboelectric materials could be divided into four kinds: polymer-metal [72][73][74][75][76][77][78][79][80], polymer-polymer [81-84], 6 Research polymer-semiconductor [85][86][87], and others [88][89][90][91][92]. The summarization of materials and fabrication of TENGs are shown in Table 2.…”
Section: Triboelectric Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the difference between two materials is bigger, the corresponding charge transfer amount is larger, and the output of the prepared TENG is higher. The triboelectric materials could be divided into four kinds: polymer-metal [72][73][74][75][76][77][78][79][80], polymer-polymer [81-84], 6 Research polymer-semiconductor [85][86][87], and others [88][89][90][91][92]. The summarization of materials and fabrication of TENGs are shown in Table 2.…”
Section: Triboelectric Materialsmentioning
confidence: 99%
“…The as-fabricated TENG could harvest energy from various types of irregular movements with the stretch ability from the TPU/Ag layer. The stretchable and tailorable TENG has been applied in both biomechanical monitoring and energy [98] Power source [84,87] Sensor [83,84,97,98] Polymer-semiconductor Power source [90,109] Sensor [88,91,103,109] 8 Research [101]. A flexible and modified PDMS film was applied as triboelectric layer, and the Au deposited on the backside of PDMS was selected as one electrode of TENG (Figure 4(e)).…”
Section: Polymer-polymermentioning
confidence: 99%
“…It was observed that the output resistance was inversely proportional to the applied force in the range of 0.5-10 N (10-200 kPa), thus demonstrating that the MWCNT/PDMS nanocomposite exhibits a piezoresistive response. Several factors can affect the resistance change as a function of the applied pressure of the composite containing a conductive filler in a polymeric matrix [23,24]. This includes the filler intrinsic resistance, which changes because it is elastically deformed under pressure.…”
Section: Different Mwcnt Doping Ratiosmentioning
confidence: 99%
“…The yarns were composed of flexible piezoelectric nanofibers of BNT-ST and PVDF-TrFE by electrospinning. Muhammad et al [141] fabricated a woven triboelectric nanogenerator using commercial nylon cloth and PVDF nanofibers, which can harvest energy from human motions. A woven triboelectric nanogenerator harvests energy from human movement; a schematic diagram of the production process of this device is shown in Figure 10b.…”
Section: Energy Harvesting Devicementioning
confidence: 99%